Sharp Toroidal Resonances in Planar Terahertz Metasurfaces. Issue 37 (15th July 2016) - Gupta, Manoj; Savinov, Vassili; Xu, Ningning; Cong, Longqing; Dayal, Govind; Wang, Shuang; Zhang, Weili; Zheludev, Nikolay I.; Singh, Ranjan
Abstract : A toroidal dipole in metasurfaces provides an alternate approach for the excitation of high‐ Q resonances. In contrast to conventional multipoles, the toroidal dipole interaction strength depends on the time derivative of the surrounding electric field. A characteristic feature of toroidal dipoles is tightly confined loops of oscillating magnetic field that curl around the fictitious arrow of the toroidal dipole vector.